2021
DOI: 10.1177/0363546520988172
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Differences Exist Between the Fastball, Changeup, Curveball, and Dropball Pitch Types in Collegiate Softball Pitchers

Abstract: Background: A majority of softball literature focuses on the mechanics associated with pain and injury within a single pitch type per study; however, the generalizability of these findings is unknown since a kinematic comparison has yet to be performed between pitch types. Understanding kinematic differences between pitch types can be used to identify risk factors for injury, improve safety guidelines, and improve performance by linking specific mechanics with desired pitch outcomes. Hypothesis/Purpose: The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We also identified softball curveballs that cause lateral deviation of the ball. For this pitch variation, Downs et al 14 reported similar elbow and thorax kinematics to other pitches 49,56,70 indicating that athletes alter other variables that were not measured. While it is well understood how baseball pitching techniques cause lateral deviation of fastballs, it remains unclear how softball pitchers throw curveballs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We also identified softball curveballs that cause lateral deviation of the ball. For this pitch variation, Downs et al 14 reported similar elbow and thorax kinematics to other pitches 49,56,70 indicating that athletes alter other variables that were not measured. While it is well understood how baseball pitching techniques cause lateral deviation of fastballs, it remains unclear how softball pitchers throw curveballs.…”
Section: Discussionmentioning
confidence: 70%
“…9 Softball pitchers use changeups disguised as fastballs, which arrive later and experience a greater reduction in vertical height due to a slower release speed. 14 Similarly, the dropball pitch is also thrown to appear as a fastball but often has a greater reduction in vertical height due to topspin imparted on the ball. 14 We identified two investigations of softball changeup and dropball pitches in this review.…”
Section: Discussionmentioning
confidence: 99%
“…First, only the fastball pitch was analyzed; however, prior research showed that elbow flexion does not vary between the fastball, curveball, changeup, and drop-ball pitch types. 5 Second, only the acceleration phase of the pitch was analyzed. Previous research noted that elbow flexion is greatest during the initial upswing of the pitching arm in preparation for the acceleration phase and during follow-through, 10 while the largest shoulder distraction forces occur during the acceleration phase of the pitch.…”
Section: Discussionmentioning
confidence: 99%
“…4,28 The full-body dynamic motion of the windmill softball pitch also requires the arm to make an approximately 485 arc of motion. 4 The elbow of the throwing arm is mostly extended throughout the circumducted movement 5 and likely contributes to centrifugal distraction force on the shoulder. An extended elbow may also lead to greater ball velocities by mechanically creating a longer lever arm during circumduction, whereas a pitching arm with greater elbow flexion would result in a shorter lever arm.…”
mentioning
confidence: 99%
“…The limited data in the existing softball literature indicate that trunk kinematics vary among pitch type. 5 Most prior investigations have focused on descriptive kinematic and kinetic data while pitching the fastball, 4 , 16 , 40 , 41 with a small number of studies examining select trunk and shoulder kinematics and kinetics in relation to pain prevalence for the rise-ball and changeup pitches. 17 19 Therefore, there are limited data examining joint loads about the upper extremity and pain prevalence across multiple pitch types.…”
mentioning
confidence: 99%